2015
DOI: 10.17700/jai.2015.6.2.179
|View full text |Cite
|
Sign up to set email alerts
|

Gender Analysis of Agricultural Innovation and Decision Making among Rice Farming Household in Nigeria

Abstract: A B S T R A C TRice importance in food security and contribution to Nigeria economy cannot be overlooked, rice is produced in Nigeria but productivity increase has been a challenge due to many factors. Actors involved in the production process include women who are faced with formidable obstacles. This research analyze agricultural innovation, constraints faced by male and female rice farming households and decision making among rice farming household in Nigeria rice hub. A 3-stage stratified random sampling p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 4 publications
(2 reference statements)
2
4
2
Order By: Relevance
“…Other reasons are high level of household size, high rate of sea pirate activities (raping, robbing, kidnaping and assault), differences in harvesting experience, time of working hours and high level engagement of women in many other fishing activities such as processing, marketing and fetching of fire wood. However, the result disagree with [33] and [34]. who reported that male headed households in the region and the country respectively are likely to be poor than the female headed households .…”
Section: Poverty Status Of Male and Female Crayfish Harvesterscontrasting
confidence: 90%
See 1 more Smart Citation
“…Other reasons are high level of household size, high rate of sea pirate activities (raping, robbing, kidnaping and assault), differences in harvesting experience, time of working hours and high level engagement of women in many other fishing activities such as processing, marketing and fetching of fire wood. However, the result disagree with [33] and [34]. who reported that male headed households in the region and the country respectively are likely to be poor than the female headed households .…”
Section: Poverty Status Of Male and Female Crayfish Harvesterscontrasting
confidence: 90%
“…This is in support of [36] findings among smallholders' farmers in South Eastern Nigeria and [37] findings among youth farmers in Akwa Ibom State. Conversely, the findings disagrees with [38,39,40] who reported farm and rural household males to be poorer than females in Ogun State, Oyo State and Nasarawa/Benue of Nigeria respectively. This may be due to regional, environmental, job and /or type of farm differences.…”
Section: Poverty Status Of Male and Female Crayfish Harvesterscontrasting
confidence: 85%
“…L is the number of hours of the plot manager's labor on the farm per day. X is the vector of k which represents other inputs (improved seeds, pesticides, fertilizer, agricultural implements 6 , and hired labor). With respect to farm inputs, if any input shows significant negative impact on the output of any particular crop, it implies that the input in question is not an input required to produce such crop.…”
Section: Solomon Abayomi Olakojomentioning
confidence: 99%
“…As propounded by institutions affiliated with the ARC and studies connected to major breeding and dissemination initiatives, it is argued that NERICA varieties have various technical advantages over African and Asian rice counterparts on the basis of nutrient responsiveness, early flowering, grain count, grain weight per panicle, grain resistance to mill shattering, pest and drought resistance, high protein content, along with good taste and aroma (AfricaRice, 1995(AfricaRice, , 2002(AfricaRice, , 2011. On this basis, NERICA has been promoted as a tool for livelihood improvement that can contribute to increased incomes, self-sufficiency and even gender equality (Ajewole et al, 2015;Makosa and Takayanagi, 2014). In a more dramatic fashion, claims of an African 'miracle rice' -echoing those that accompanied the original Green Revolution variety IR-8 in Asia -appeared within the media (Harsch, 2004).…”
Section: Nerica and Livelihood Change In Upland Ugandamentioning
confidence: 99%